ANALYSIS OF MATHEMATICAL CRITICAL THINKING ABILITIES OF ELEMENTARY SCHOOL STUDENTS - Liyana Sunanto; Khoimatun; Ahmad Yusron; Pipit Nurossobah; Nurbaetullah Karnita (Jurnal Cakrawala Pendas, 2025)
This study aims to analyze elementary school students’ mathematical critical thinking skills through a Systematic Literature Review (SLR) approach based on the PRISMA guidelines. A total of 20 articles published between 2015 and 2025 were obtained from the Google Scholar and Publish or Perish databases and systematically analyzed through identification, selection, and content analysis stages. The review results indicate that learning models such as Problem Based Learning (PBL), Discovery Learning, and Realistic Mathematics Education (RME) are the most widely applied and proven effective in enhancing students’ mathematical critical thinking skills. Furthermore, digital learning media such as investigation-based e-LKPDs, contextual mathematics comics, and interactive multimedia contribute positively to improving conceptual understanding and analytical ability. Several studies also highlight common challenges, including teachers’ limited pedagogical competence and students’ low learning motivation. Overall, this literature synthesis provides a comprehensive overview of trends, effectiveness, and challenges in developing mathematical critical thinking skills among elementary school students in Indonesia.